2019
DOI: 10.1111/trf.15546
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical development of a cryopreservable megakaryocytic cell product capable of sustained platelet production in mice

Abstract: BACKGROUND Platelet (PLT) transfusions are the most effective treatments for patients with thrombocytopenia. The growing demand for PLT transfusion products is compounded by a limited supply due to dependency on volunteer donors, a short shelf‐life, risk of contaminating pathogens, and alloimmunization. This study provides preclinical evidence that a third‐party, cryopreservable source of PLT‐generating cells has the potential to complement presently available PLT transfusion products. STUDY DESIGN AND METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Yet, here the premature MK progenitors were cryopreserved, which could be potentially less challenging due to a less complex state of the membrane in comparison to mature MKs, and would require subsequent maturation of MK progenitors after thawing prior to potential application in a patient. The 10% DMSO-based CryoStor medium also provided sufficient recovery after cryopreservation for MKs generated from CD34+ umbilical cord blood cells [ 69 ]. In this case, MK generation approach is donor dependent and limited to proliferation capacity of primary umbilical cord cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, here the premature MK progenitors were cryopreserved, which could be potentially less challenging due to a less complex state of the membrane in comparison to mature MKs, and would require subsequent maturation of MK progenitors after thawing prior to potential application in a patient. The 10% DMSO-based CryoStor medium also provided sufficient recovery after cryopreservation for MKs generated from CD34+ umbilical cord blood cells [ 69 ]. In this case, MK generation approach is donor dependent and limited to proliferation capacity of primary umbilical cord cells.…”
Section: Discussionmentioning
confidence: 99%
“…Though transfusion of cryopreserved PLTs have been shown in experimental clinical trials already in the late 1970s, up to now cryopreserved PLTs are not routinely applied in transfusion medicine practice [ 71 ]. Thus, in terms of biobanking strategy for clinical application, it seems more feasible to focus on rather cryopreserving MKs or MK-precursors, then the PLTs per se [ 7 , 13 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, because of the unique ability of these ASCLs to produce endogenous TPO through transferrin stimulation, TPO does not need to be added to the media. Meanwhile, Patel et al reported a scaled-up induction of cryopreservable megakaryocytes from human cord blood HSCs through an optimized culture condition [78]. While these induced megakaryocytes have not produced platelets at the clinically required quantity and quality, the findings may contribute to improved ex vivo platelet production.…”
Section: Establishment Of Expandable Megakaryocytic Cell Lines Througmentioning
confidence: 99%
“…In the case of pluripotent stem cells, such as ESCs or iPSCs, the process of cytokine-induced MK differentiation includes the following steps: 1) culturing and expansion of initial cell line, 2) mesoderm induction, 3) forwarding the cell fate into hematopoietic progenitors, and, finally, 4) induction of megakaryopoiesis and thrombopoiesis. Cytokine-induced differentiation showed to be a robust method enabling the possibility to upscale the process in bioreactor systems and delivering MKs and PLTs that show functionality in vivo ( 32 , 47 , 56 , 60 , 63 , 64 ).…”
Section: Producing Mks and Platelets In Vitromentioning
confidence: 99%